When ecosystem services interact: crop pollination benefits depend on the level of pest control - Lundin, Ola (The Royal Society, 2013)
Pollination is a key ecosystem service which most often has been studied in isolation although effects of pollination on seed set might depend on, and interact with, other services important for crop production. We tested three competing hypotheses on how insect pollination and pest control might jointly affect seed set: independent, compensatory or synergistic effects. For this, we performed a cage experiment with two levels of insect pollination and simulated pest control in red clover (Trifolium pratense L.) grown for seed. There was a synergistic interaction between the two services: the gain in seed set obtained when simultaneously increasing pollination and pest control outweighed the sum of seed set gains obtained when increasing each service separately. This study shows that interactions can alter the benefits obtained from service-providing organisms, and this needs to be considered to properly manage multiple ecosystem services.